2016
DOI: 10.1653/024.099.0420
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Fauna Associated withAedes aegypti(Diptera: Culicidae) in Yucatán State of Southeastern México, and Checklist with New Records

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…aegypti , consistent with previous studies performed in Merida. Diversity of mosquito species represented 17.3% (9/52) of mosquito fauna identified in Yucatan State 25 . Other mosquito species involved in arbovirus disease transmission were also identified including Cx.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , consistent with previous studies performed in Merida. Diversity of mosquito species represented 17.3% (9/52) of mosquito fauna identified in Yucatan State 25 . Other mosquito species involved in arbovirus disease transmission were also identified including Cx.…”
Section: Discussionmentioning
confidence: 99%
“…For the state of Yucatan, Ibáñez-Bernal and colleagues 5 reported 45 species, whereas Ibáñez-Bernal 6 registered 11 genera and 30 species for Yucatan. Nájera-Vázquez and colleagues 27 registered eight genera and 19 species of mosquitoes for the state of Yucatan; Zapata-Peniche and colleagues 28 reported four genera and 12 species in the city of Mérida, Yucatan; Dzul-Manzanilla and colleagues 29 registered nine genera and 22 species for the state of Yucatan; and recently, Baak-Baak and colleagues 15 reported seven genera and 27 species for the same state. In the present study, the state of Yucatan was found to include 11 genera and 34 species.…”
Section: Discussionmentioning
confidence: 99%
“…A database was constructed from collections reported in Baak-Baak and colleagues, 15,16 this study, and the Global Biodiversity Information Facility (GBIF, www. gbif.org/).…”
Section: Ecological Niche Models (Enm)mentioning
confidence: 99%
“…pseudopunctipennis in a cenote (its natural, permanent habitat) at 20 masl. 30 On the other hand, there is a negative association with water turbidity, which indicates that females prefer to lay their eggs in clear rather than turbid water. This coincides with a previous report from 10 countries, spanning most of the geographic range of the species, whose larvae were found in clear-water breeding sites in 90% of the cases (i.e.…”
Section: Discussionmentioning
confidence: 99%